The complete Beatles: The official story of the Abbey Road years 1962-1970 - Lewisohn, Mark 1958- (hamlyn, 2018)
After years out of print, a new edition of this hotly sought-after classic is available again! Mark Lewisohns definitive guide covers every recording session done by the Beatles at EMIs famed Abbey Road recording studio. It includes the number of takes for each song; who contributed what; previously unpublished studio documents and interviews with many of the key recording personnel; and facsimile reproductions of Abbey Road recording sheets, tape boxes, album sleeve roughs, memos, contracts, press releases and more. Lavishly illustrated with over 350 photographs (rare images by Linda McCartney among them), this must-have volume also features an exclusive introductory interview with Paul McCartney.